Social representations of the female teenager concerning the sexuality in aids time - Azevedo, Regina Lígia W; Fonseca, Aline A; Coutinho, Maria da Penha L; Saldanha, Ana Alayde W (Brazilian Journal of Sexually Transmitted Diseases, 2006)
Introduction: The sexuality is an inherent phenomenon to the human being, and it’s in the adolescence that it starts to be lived deeply with more intensity.Objective: to apprehend the Social Representation of the adolescents of the female gender concerning the sexuality, associated with the aids. Methods: Theresearch was developed in public and private schools of the city of João Pessoa/PB, with the participation of 110 feminine adolescents, with age between 12and 19 years old. For the collection of the data the Free Technique of Association of Words was used and these words were processed through the software Tri-Deux-Mots and analyzed through the Factorial Analysis of Correspondence (AFC). Results: The results had demonstrated that aids is incorporated in thecognitive and affective universes of the young girls, that is apprehended from symbols and meanings that compose their social relations. Articulating socialrepresentations, practical relations of sort, vulnerability and of aids prevention is to confront with a heterogeneous whole, where contradictions, similarities,cognition, affection, emotions, rationality and many other conditions that are gifts in their daily and that increase the vulnerability to the infection of DST/aidsare expressed. The Social Representation (RS) of the female gender adolescents concerning sexuality was identified associating them to questions of thevulnerability to the HIV/aids, taking the elements of their cognitive, affective and social spheres into consideration. Conclusion: It was observed that,although the adolescents have knowledge of aids and its forms of prevention, they continue in situation of vulnerability due to the psychological, social-economic and cultural aspects.